MENINGKATKAN KREATIVITAS PADA REMAJA MELALUI PELATIHAN DAN PEMBUATAN BUCKET SNACK SEBAGAI PELUANG USAHA - Riyadini Riyan Utami; Viola De Yusa; Besti Lilyana (Universitas Mataram, 2023)
This Community Service Activity (PKM) is targeted at teenagers with the aim of providing insight and creativity to youth. The object of service is located in Wayhalim Bandar Lampung, namely teenagers in the RT 1 Wayhalim Bandar Lampung environment. In Community Service activities carried out by the service team, the solution offered to youth is to make snack buckets as a business opportunity. The method used in Community Service activities is starting from a location survey, direct discussions with the head of the RT, outreach and training. The training is carried out face to face. The PKM team provided outreach about the importance of entrepreneurship in order to generate income that has economic value. In the second stage, the PKM team provided practical training on making bucket snacks. The results of Community Service activities that have been carried out are having a positive impact on youth. They become inspired and can be enthusiastic about doing business and entrepreneurship, because from this business they will get income and also opportunities for entrepreneurship. The results of the snack buckets were distributed to the participants as an appreciation of the results of the practice and in the future they could continue as independent businesses for teenagers. Based on a survey conducted with several participants who were attended by 20 participants, many participants were interested in starting a bucket snack business or entrepreneurship because they had very good opportunities.